New Class of Pseudorandom Number Generators for Logic Encryption Realization - Chugunkov, Ilya V.; Kliuchnikova, Bogdana V.; Ivanov, Michael A.; Salikov, Evgenii A.; Zubtsov, Artem O. (IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference, 2020)
Pseudorandom number generators (PRNG) are essential elements of any security system. In the tusks of information security PRNG provide unpredictable operation of protection means and methods. There is considered new class of sequences in the paper, which are formed by non-linear feedback shift registers, whose structures are determined by characteristical polynomials in the N-th order over GF(2 n ) field in the form of (x - 1)Φ(x), where Φ(x) is the (N - 1)-th degree polynomial is primitive over GF(2 n ) field. Proposed devices are assumed for hardware obfuscation concept realization.